Transdiagnostic assessment of repetitive negative thinking and responses to positive affect: Structure and predictive utility for depression, anxiety, and mania symptoms - McEvoy, Peter; Hyett, M.; Ehring, T.; Johnson, S.; Samtani, S.; Anderson, Rebecca; Moulds, M. (Elsevier BV, 2018)
Background: Repetitive negative thinking (RNT) is a cognitive process that is repetitive, passive, relatively uncontrollable, and focused on negative content, and is elevated in emotional disorders including depression and anxiety disorders. Repetitive positive thinking is associated with bipolar disorder symptoms. The unique contributions of positive versus negative repetitive thinking to emotional symptoms are unknown. The first aim of this study was to use confirmatory factor analyses to evaluate the psychometrics of two transdiagnostic measures of RNT, the Repetitive Thinking Questionnaire (RTQ-10) and Perseverative Thinking Questionnaire (PTQ), and a measure of repetitive positive thinking, the Responses to Positive Affect (RPA) Questionnaire. The second aim was to determine incremental predictive utility of these measures. Method: All measures were administered to a sample of 2088 undergraduate students from the Netherlands (n = 992), Australia (n = 698), and America (n = 398). Results: Unidimensional, bifactor, and three-factor models were supported for the RTQ-10, PTQ, and RPA, respectively. A common factor measured by all PTQ items explained most variance in PTQ scores suggesting that this measure is essentially unidimensional. The RNT factor of the RTQ-10 demonstrated the strongest predictive utility, although the PTQ was also uniquely although weakly associated with anxiety, depression, and mania symptoms. The RPA dampening factor uniquely predicted anxiety and depression symptoms, suggesting that this scale is a separable process to RNT as measured by the RTQ-10 and PTQ. Limitations: Findings were cross-sectional and need to be replicated in clinical samples. Conclusions: Transdiagnostic measures of RNT are essentially unidimensional, whereas RPA is multidimensional. RNT and RPA have unique predictive utility.